5(r-1)=2(1-r)

Simple and best practice solution for 5(r-1)=2(1-r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(r-1)=2(1-r) equation:


Simplifying
5(r + -1) = 2(1 + -1r)

Reorder the terms:
5(-1 + r) = 2(1 + -1r)
(-1 * 5 + r * 5) = 2(1 + -1r)
(-5 + 5r) = 2(1 + -1r)
-5 + 5r = (1 * 2 + -1r * 2)
-5 + 5r = (2 + -2r)

Solving
-5 + 5r = 2 + -2r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '2r' to each side of the equation.
-5 + 5r + 2r = 2 + -2r + 2r

Combine like terms: 5r + 2r = 7r
-5 + 7r = 2 + -2r + 2r

Combine like terms: -2r + 2r = 0
-5 + 7r = 2 + 0
-5 + 7r = 2

Add '5' to each side of the equation.
-5 + 5 + 7r = 2 + 5

Combine like terms: -5 + 5 = 0
0 + 7r = 2 + 5
7r = 2 + 5

Combine like terms: 2 + 5 = 7
7r = 7

Divide each side by '7'.
r = 1

Simplifying
r = 1

See similar equations:

| 5+2=310 | | 3cos^2(x)-8cos(x)+4=0 | | 0.60*x=96 | | 4x^2+3x+7x^2-x-5x^2= | | 4-4(k-5)=2(2-k)6 | | 6(0)-6y=12 | | x*0.1=200 | | y/4x20/x | | 3/8*9/11 | | 5k-8=3 | | 4x+9=6x-x | | 8x-(2x+5)=5x+(3x-8) | | x-4/​5=7 | | 27x^2-27x-35=0 | | (3/8)/9/11 | | (25-2x)(20-2x)(x)= | | y^2*(2.9-y)-1.25=0 | | 16/4x(4)= | | 3-2x=11+2x | | 24=6*b*(1/2) | | 24=6b/2 | | 2a+1/2=3a-1/4 | | 3x^6+9x^4-30x^2=0 | | 7x+1y=80000 | | (16/81)3/4 | | 2cos^2x+3sinx+3=0 | | Y/-12=-36 | | (1-3i)*(5-2zi)=(2i-3)*(3z+2i) | | 3x-(1/7)x=120 | | 4xsquared-8x= | | 8x+9x=37 | | 5(h+1)+3(h-2)=12 |

Equations solver categories